Aerogel reinforced ship antifouling paint and preparation method thereof
By combining perfluorinated chemistry with silicon-oxygen chemistry to prepare fluorosilicone prepolymers and superhydrophobic aerogels, and synthesizing chromium-based metal-organic framework composites and ionic liquids, the problems of durability and surface degradation of ship antifouling coatings in the marine environment were solved, and a highly efficient antifouling and mechanically stable coating was achieved.
Patent Information
- Application Number
- CN202510982611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2045-07-16
AI Technical Summary
The durability and surface properties of existing ship antifouling coatings degrade in dynamic marine environments, making it difficult to simultaneously cope with multiple destructive factors such as physical friction, chemical erosion, and biological action. Traditional coatings are prone to microcracks and biological attachment.
By combining perfluorinated chemistry with silicon oxide chemistry, fluorosilicone prepolymers were prepared as the resin matrix. Superhydrophobic aerogels were prepared by hydrolysis of ethyl orthosilicate and perfluorinated surface modification. Chromium-based metal-organic framework composites were synthesized and ionic liquids were introduced. Combined with emulsion polymerization and etching technology, multi-level structured microsphere additives were prepared to form a synergistic coating of resin matrix, aerogel, ionic liquid composite additive and microsphere additive.
It improves the coating's anti-adhesion performance and mechanical stability, has anti-fouling properties and durability, can effectively resist biological adhesion and chemical erosion in the marine environment, and extend the coating's service life.
Smart Images

Figure BDA0005503384770000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation and relates to an aerogel-reinforced ship antifouling coating and a preparation method thereof. Background Art
[0002] Antifouling coatings for ships are one of the key materials in the field of marine engineering. One of its core functions is to prevent the attachment and growth of marine organisms on the surface of the hull. There are a large number of microorganisms, algae, barnacles, shellfish and other organisms in the marine environment. They secrete sticky substances or directly adsorb on the surface of the hull to form a biofouling layer that increases navigation resistance. Therefore, the application of antifouling coatings is of great significance to the economy, safety and ecological protection of ships. Traditional antifouling coatings for ships mainly achieve antifouling functions through three mechanisms. The first is the physical barrier type, which works by reducing the contact area between organisms and the coating by constructing low surface energy or micro-nanoscale rough structures; the second is the chemical release type, which slowly releases biotoxic chemicals. However, with the tightening of environmental protection regulations, traditional highly toxic substances have been banned; the third is the biomimetic type.
[0003] Although antifouling coating technology has made great progress, it still faces severe challenges in practical application, mainly the two core issues of durability and surface property degradation. In a dynamic marine environment, the coating needs to deal with multiple destructive factors such as physical friction, chemical erosion, and biological action at the same time. Although the rigid network structure of the traditional resin matrix can provide initial strength, it is prone to microcracks under cyclic stress and expands into macroscopic peeling. The surface functional layer of the superhydrophobic coating often has insufficient bonding with the matrix. Under turbulent impact or sand friction, the matrix is exposed and easily attached by organisms. Aerogel materials have attracted attention due to their unique three-dimensional network structure and high specific surface area. They can not only serve as a mechanical reinforcement phase to improve the shear resistance of the coating, but their rich pore structure can also serve as a bactericide carrier to achieve controlled release. Through surface chemical modification, aerogel can simultaneously give the coating superhydrophobic properties and anti-biological adhesion ability. Therefore, it is of great significance to prepare an aerogel-reinforced ship antifouling coating. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide an aerogel-enhanced ship antifouling coating and a preparation method thereof. First, a fluorosilicone prepolymer with excellent chemical stability and low surface energy is prepared as a resin matrix by combining perfluorinated chemistry with silicon oxide chemistry; secondly, an aerogel material with super-hydrophobicity is prepared by hydrolysis of ethyl orthosilicate and perfluorinated surface modification, thereby enhancing the anti-adhesion performance and mechanical stability of the coating; thirdly, a chromium-based metal organic framework composite material is synthesized by a hydrothermal method and an ionic liquid is introduced to prepare an ionic liquid composite additive with sustained release performance; in addition, a microsphere additive with a multi-level structure is prepared by emulsion polymerization combined with an etching process to further optimize the surface function of the coating. Ultimately, the resin matrix, aerogel, ionic liquid composite additive and microsphere additive work synergistically to give the coating antifouling performance and durability, thereby meeting the needs of actual production.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing an aerogel-reinforced antifouling coating for ships, the preparation method comprising:
[0007] S1, mixing perfluorohexyl ethyl acrylate, a silane coupling agent and azobisisobutyronitrile to react to obtain a fluorosilicone prepolymer, and mixing the fluorosilicone prepolymer, hydroxyl-terminated PDMS, dibutyltin dilaurate and PEEK nanofibers to obtain a resin matrix;
[0008] S2, mixing and hydrolyzing ethyl orthosilicate, an ethanol aqueous solution and an ammonia aqueous solution to obtain a SiO2 gel, mixing the SiO2 gel with a PDMS prepolymer to obtain a wet gel, performing solvent replacement to obtain a replacement gel, and immersing the replacement gel in an ethanol aqueous solution of per(heptadeca)fluorodecyltriethoxysilane to obtain an aerogel;
[0009] S3, dispersing chromium nitrate nonahydrate and terephthalic acid in a DMF aqueous solution to react to obtain product A, and then immersing product A in a [BMIM]PF6 methanol solution to obtain an ionic liquid composite additive;
[0010] S4, mixing cyclohexane, Span80 and Tween80, adding methyltriethoxysilane / quaternary ammonium salt solution, and then etching with acetic acid solution to obtain a microsphere additive;
[0011] S5, mixing the resin matrix, the aerogel, the ionic liquid composite additive, the microsphere additive and the solvent to obtain an aerogel-reinforced ship antifouling coating.
[0012] Specifically include:
[0013] S1, mixing perfluorohexyl ethyl acrylate, a silane coupling agent, and azobisisobutyronitrile, adjusting the reaction temperature to a first temperature under a nitrogen atmosphere to obtain a fluorosilicone prepolymer, mixing the fluorosilicone prepolymer, hydroxyl-terminated PDMS, dibutyltin dilaurate, and PEEK nanofibers, adjusting the temperature to a second temperature with stirring, and ultrasonically dispersing the mixture to obtain a resin matrix;
[0014] S2, mixing and hydrolyzing tetraethyl orthosilicate, an ethanol aqueous solution, and an ammonia aqueous solution to obtain a SiO2 gel, mixing the SiO2 gel with a PDMS prepolymer, adjusting the temperature to a third temperature and stirring to obtain a wet gel, then performing solvent replacement to obtain a replacement gel, immersing the replacement gel in an ethanol aqueous solution of per(heptadecafluorodecyltriethoxysilane), adjusting the temperature to a second temperature and stirring, and vacuum drying to obtain an aerogel;
[0015] S3, dispersing chromium nitrate nonahydrate and terephthalic acid in a DMF aqueous solution, adjusting the temperature to a fourth temperature for hydrothermal reaction to obtain product A, then immersing product A in a [BMIM]PF6 methanol solution, and vacuum drying to obtain an ionic liquid composite additive;
[0016] S4, mixing cyclohexane, Span80 and Tween80, adjusting the pH to a specified value with aqueous ammonia, adding methyltriethoxysilane / quaternary ammonium salt solution, stirring, and etching with acetic acid solution to obtain a microsphere additive;
[0017] S5, mixing the resin matrix, the aerogel, the ionic liquid composite additive, the microsphere additive and the solvent to obtain an aerogel-reinforced ship antifouling coating.
[0018] The synthesis of fluorosilicone prepolymers is based on the principle of free radical polymerization. Its core principle is to activate the double bonds of the fluorinated monomers with an initiator, initiating a chain propagation reaction. A silane coupling agent is also introduced to functionalize the molecular chain. Perfluorohexylethyl acrylate, the primary monomer, contains an unsaturated double bond in the acrylate group of its molecular structure. Azobisisobutyronitrile, the initiator, generates free radicals upon heating. These radicals attack the double bonds of the perfluorohexylethyl acrylate, initiating chain propagation and forming a polymer backbone with fluorocarbon chains as the backbone. The introduction of the silane coupling agent KH560 imparts the key siloxane functional groups to the prepolymer. The KH560 molecule contains two reactive groups: an epoxy group at one end and a methoxysilane group at the other. Under high-temperature reaction conditions, the ring-opening of the epoxy groups exposes hydroxyl groups, which react with free radicals at the end of the perfluorohexylethyl acrylate chain or with reactive sites within the existing polymer chain, thereby embedding siloxane structural units into the fluorocarbon backbone. This chemical bonding not only achieves molecular-level hybridization between fluorocarbon chains and siloxane chains, but also provides the prepolymer with anchoring points for subsequent reactions with inorganic fillers (such as silica aerogel) or organosilicon polymers (such as hydroxyl-terminated PDMS). Furthermore, the methoxysilane groups of KH560 can be converted into silanol groups during the subsequent hydrolysis process, providing chemical bonding capability for the interfacial bonding between the resin matrix and the reinforcement phase.
[0019] After the fluorosilicone prepolymer is synthesized, it is then composited with hydroxyl-terminated polydimethylsiloxane (PDMS) through a condensation cross-linking reaction to construct a three-dimensional network structure. Nano-reinforcement phases are then introduced to enhance mechanical properties. Hydroxyl-terminated PDMS is a linear silicone polymer with reactive hydroxyl groups at both ends of its molecular chain. These hydroxyl groups, under the action of a catalyst, undergo a condensation reaction with the methoxysilane groups in the fluorosilicone prepolymer, connecting the linear fluorosilicone prepolymer and PDMS into a three-dimensional network structure. The formation of this cross-linked network imparts excellent elasticity and deformation recovery to the resin matrix. The rigid structure of the fluorocarbon segments provides compression resistance and low surface energy, while the flexible siloxane chains of PDMS absorb external stress through curling and slipping of the molecular chains, preventing brittle fracture. To further enhance the material's impact and wear resistance, polyetheretherketone (PEEK) nanofibers, a semi-crystalline, high-performance engineering plastic, were introduced as a reinforcement phase. PEEK nanofibers were uniformly distributed throughout the resin matrix using high-energy ultrasonic dispersion. These fibers work through two mechanisms: first, they act as rigid fillers to directly bear external stress and consume fracture energy through crack deflection and fiber pull-out effect; second, the abundant functional groups (such as ketone groups) on the fiber surface form hydrogen bonds or van der Waals forces with polar groups in the resin matrix, enhancing the interfacial bonding strength.
[0020] Using ethyl orthosilicate as a silicon source, the ethoxy groups in its molecules undergo nucleophilic substitution with water under alkaline conditions, gradually generating silicic acid monomers. Ammonia, acting as a weak base, activates water molecules by deprotonation, accelerating the hydrolysis of the ethoxy groups. Silicic acid monomers connect through dehydration or dealcoholization reactions, forming Si-O-Si bonds. In an alkaline environment, the condensation reaction tends to produce linear structures with few branches. However, with prolonged reaction time, these linear chains undergo further cross-linking, gradually forming a nanostructured network with mesoscopic pores. After the silica gel is formed, polydimethylsiloxane (PDMS) prepolymer is introduced to construct an organic-inorganic hybrid network. The addition of PDMS achieves structural enhancement through a two-step mechanism: first, the silicon-hydrogen bonds in the PDMS prepolymer undergo condensation reaction with the silanol groups on the silica surface under heating conditions to form a covalently linked Si-O-Si bridging structure. This chemical bonding anchors the flexible PDMS segments to the rigid silica skeleton, effectively alleviating external stress concentration and preventing brittle fracture; second, the unreacted PDMS prepolymer fills the silica nanopores through physical infiltration, forming an elastic support body during the subsequent curing process, further enhancing the resilience of the aerogel.
[0021] Solvent replacement in the wet gel is a key step in preventing pore structure collapse during drying. Ethanol is used to displace water molecules in the gel, leveraging the miscibility of ethanol with water to completely remove any residual moisture. This is followed by a transition to an ethanol-n-hexane solvent mixture, gradually reducing the system's polarity. Finally, pure n-hexane, as the low-surface-tension solvent, completes the replacement. n-Hexane was chosen for its low surface tension, significantly reducing capillary forces during evaporation, thereby minimizing compression deformation of the pore structure. Furthermore, n-hexane's excellent compatibility with PDMS prevents solvent-polymer phase separation. The dried aerogel undergoes surface chemical modification to impart superhydrophobic properties. Perfluorodecyltriethoxysilane is used as a modifier. The ethoxysilane ends of its molecules react with the silanol groups on the aerogel surface to form a dense, low-surface-energy coating. This modification not only reduces surface energy but also further refines surface roughness through the perfluorinated chains. The chemical inertness of the fluorinated layer effectively resists oxidizing agents in marine environments, extending the coating's service life. The resin matrix and the aerogel form a rigid-flexible interpenetrating structure through covalent bonds and physical entanglement. The condensation crosslinking of the fluorosilicone prepolymer and PDMS gives the coating elastic deformation ability, while the nanoporous skeleton of the aerogel absorbs external stress through crack deflection and energy dissipation mechanisms. This rigid-flexible synergy not only improves the impact resistance of the coating, but also inhibits phase separation through interfacial chemical compatibility. PEEK nanofibers serve as a reinforcing phase, connecting the resin and aerogel interface through a bridging effect. Their high modulus properties evenly transfer local stress to the aerogel skeleton, avoiding coating peeling caused by stress concentration. At the same time, after the aerogel surface is modified with fluorosilane, its low surface energy forms a chemically compatible interface with the fluorosilicone resin matrix, further strengthening the interfacial bonding strength and forming a dual mechanical-chemical synergy.
[0022] Chromium nitrate nonahydrate, a chromium source, coordinates with the carboxylic acid groups of terephthalic acid. The bidentate ligand, after deprotonation of its two carboxylic acid groups, forms stable coordination bonds with trivalent chromium ions via oxygen atoms, forming a MOF. Each trivalent chromium ion is coordinated with three terephthalic acid ligands, creating a cage-like pore structure. The loading of the ionic liquid is based on the synergistic effect of capillary adsorption and surface interactions. During the impregnation process, the MOF mesopores draw the ionic liquid solution into the pores through capillary forces. The imidazolium cations of the ionic liquid form stable bonds with the carboxylic acid groups in the MOF backbone through electrostatic attraction and π-π stacking, while the hexafluorophosphate anions occupy the remaining pore space through space filling. After loading, the solvent is removed by vacuum drying, and the ionic liquid molecules are confined within the MOF pores, forming a complex system of physical adsorption and chemical bonding. The stability of the MOF backbone in seawater is affected by factors such as pH and ionic strength. When the MOF on the coating surface comes into contact with seawater, chloride ions gradually replace hexafluorophosphate ions through ion exchange, disrupting the original electrostatic balance and prompting the slow release of imidazolium cations from the pores. At the same time, cations such as sodium and magnesium ions in seawater can compete for coordination with trivalent chromium ions in the MOF framework, further weakening the framework structure and accelerating the diffusion and release of the ionic liquid. The released imidazolium cations disrupt the charge balance of the microbial cell membrane, leading to membrane potential disorder and leakage of contents, thereby prolonging the antifouling effect. Under the high salinity and weak alkalinity of seawater, the MOF framework needs to resist hydrolysis and ion corrosion. The strong coordination bond between trivalent chromium ions and carboxylic acid ligands gives MOF high hydrolysis resistance, while the hydrophobic ionic liquid layer can partially block direct contact between water molecules and the framework. In addition, the mesoporous structure of MOF allows the ionic liquid to be released slowly, avoiding the sudden release effect caused by excessively high concentrations in a short period of time, thereby reducing toxic effects on non-target organisms.
[0023] Span80 and Tween80 are nonionic surfactants, with molecular structures consisting of lipophilic hydrocarbon chains and hydrophilic polyethylene glycol chains. In a mixed system of oil and aqueous phases, an oil-in-water microemulsion is formed. Methyltriethoxysilane, the silicon source, undergoes gradual hydrolysis and condensation of the ethoxy groups in its molecule in the alkaline water core. Methyltriethoxysilane hydrolyzes to methylsilanol. The highly reactive hydroxyl groups carried by the hydrolysis product form Si-O-Si bonds via dehydration reactions between adjacent silanol molecules, initially forming linear or cyclic oligosiloxanes. Within the microemulsion system, the spatial arrangement of the oligomers is strictly constrained, forcing the molecules to adopt the lowest energy configuration: a highly symmetrical cage structure. This structure is formed by the synergistic effect of the tetrahedral bond angles of the silicon-oxygen bonds and steric hindrance: each silicon atom is connected to three bridging oxygens and one methyl group, and the eight silicon atoms are closed together by oxygen bridges to form a cubic skeleton with an internal cavity. When a quaternary ammonium salt solution is added to the initial hydrolysis phase of methyltriethoxysilane, its cationic head groups bind to the negatively charged silanols through electrostatic attraction, while the long-chain alkyl groups embed themselves into the forming POSS organic shell through hydrophobic interactions. As the condensation reaction proceeds, the quaternary ammonium salt molecules are gradually encapsulated within the POSS backbone, forming a core-shell structure. Charge complementarity between the quaternary ammonium salt's cations and the silica network plays a key role in this process: the cations neutralize the negative charge of the silanols, reducing electrostatic repulsion and promoting the condensation reaction. Simultaneously, the steric effect of the quaternary ammonium salt guides the orientation of the POSS molecules, optimizing the integrity of the cage structure. The hollowing of the silica-based microspheres relies on the selective etching of uncrosslinked silicate regions. Under acidic conditions, the incompletely condensed linear siloxane chains (containing a high number of terminal hydroxyl groups) undergo hydrolysis and cleavage first, leaving behind a hollow structure with a highly cross-linked POSS shell. When the microspheres are exposed to seawater, hydroxide ions attack the silicon-oxygen bonds in the shell, breaking some crosslinks and expanding the mesoporous channels. At the same time, chloride ions in seawater replace the counterions of the quaternary ammonium salt cations through ion exchange, disrupting the original charge balance and driving the quaternary ammonium salt to diffuse outward. Initially, the highly crosslinked regions only allow the passage of small ions. However, as the crosslinking degree decreases due to hydroxide ion erosion, larger quaternary ammonium salt molecules are released, allowing the microspheres to quickly respond to the high bacterial density at the initial stage of bioattachment while maintaining an antibacterial concentration over the long term.
[0024] As a preferred technical solution of the present invention, in S1, the mass ratio of the perfluorohexyl ethyl acrylate, the silane coupling agent and azobisisobutyronitrile is (300-330): (75-80): (2-3), for example, it can be (300, 303, 306, 309, 312, 315, 318, 321, 324, 327 or 330): (75.0, 75.5, 76.0, 76.5, 77.0, 77.5, 78.0, 78.5, 79.0, 79.5 or 80.0): (2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0), but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] In some optional examples, the silane coupling agent is KH560.
[0026] In some optional examples, the first temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional examples, the time of the first temperature reaction is 6-7h, for example, it can be 6.0h, 6.1h, 6.2h, 6.3h, 6.4h, 6.5h, 6.6h, 6.7h, 6.8h, 6.9h or 7.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional examples, the mass ratio of the fluorosilicone prepolymer, the hydroxyl-terminated PDMS, the dibutyltin dilaurate and the PEEK nanofibers is (700-730): (300-340): (7-10): (50-55), for example, it can be (700, 703, 706, 709, 712, 715, 718, 721, 724, 727 or 730): (300, 304, 308, 312, 316, 320 , 324, 328, 332, 336 or 340): (7.0, 7.3, 7.6, 7.9, 8.2, 8.5, 8.8, 9.1, 9.4, 9.7 or 10.0): (50.0, 50.5, 51.0, 51.5, 52.0, 52.5, 53.0, 53.5, 54.0, 54.5 or 55.0), but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional examples, the second temperature is 60-65°C, for example, it can be 60.0°C, 60.5°C, 61.0°C, 61.5°C, 62.0°C, 62.5°C, 63.0°C, 63.5°C, 64.0°C, 64.5°C or 65.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the second temperature stirring time is 30-40 min, for example, it can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] As a preferred technical solution of the present invention, in S2, the mass ratio of the tetraethyl orthosilicate, the ethanol aqueous solution, the ammonia aqueous solution and the PDMS prepolymer is (200-210): (220-230): (4-5): (10-12), for example, it can be (200, 201, 202, 203, 204, 205, 206, 207, 208, 209 or 210): (220, 221, 222, 223, 224, 2 25, 226, 227, 228, 229 or 230): (4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0): (10.0, 10.2, 10.4, 10.6, 10.8, 11.0, 11.2, 11.4, 11.6, 11.8 or 12.0), but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the mass ratio of ethanol to water in the ethanol aqueous solution is 4:1.
[0033] In some optional examples, the mass fraction of the ammonia solution is 20-25wt.%, for example, it can be 20.0wt.%, 20.5wt.%, 21.0wt.%, 21.5wt.%, 22.0wt.%, 22.5wt.%, 23.0wt.%, 23.5wt.%, 24.0wt.%, 24.5wt.% or 25.0wt.%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0034] In some optional examples, the hydrolysis time is 24-25h, for example, it can be 24.0h, 24.1h, 24.2h, 24.3h, 24.4h, 24.5h, 24.6h, 24.7h, 24.8h, 24.9h or 25.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the PDMS prepolymer is Sylgard 184.
[0036] In some optional examples, the third temperature is 50-55°C, for example, it can be 50.0°C, 50.5°C, 51.0°C, 51.5°C, 52.0°C, 52.5°C, 53.0°C, 53.5°C, 54.0°C, 54.5°C or 55.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, the time for adjusting the temperature to the third temperature and stirring is 12-13 hours, for example, it can be 12.0 hours, 12.1 hours, 12.2 hours, 12.3 hours, 12.4 hours, 12.5 hours, 12.6 hours, 12.7 hours, 12.8 hours, 12.9 hours or 13.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional embodiments, the solvent replacement is as follows: first, soaking in ethanol for 4-5 hours, for example, 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, changing the solution three times, and then shaking with ethanol / n-hexane with a volume ratio of 1:1 for 4-5 hours, for example, 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours. 4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, change the liquid twice, and finally soak in n-hexane for 4-5h. For example, it can be 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, change the liquid twice, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In some optional examples, the mass fraction of the per(heptadecafluorodecyltriethoxysilane ethanol solution is 5-10 wt.%, for example, it can be 5.0 wt.%, 5.5 wt.%, 6.0 wt.%, 6.5 wt.%, 7.0 wt.%, 7.5 wt.%, 8.0 wt.%, 8.5 wt.%, 9.0 wt.%, 9.5 wt.% or 10.0 wt.%, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0040] In some optional examples, the stirring time at the second temperature is 4-5h, for example, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, 4.6h, 4.7h, 4.8h, 4.9h or 5.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] As a preferred technical solution of the present invention, in S3, the mass volume ratio of the chromium nitrate nonahydrate, terephthalic acid and DMF aqueous solution is (0.8-1) g: (0.7-0.8) g: 40 mL, for example, it can be (0.80, 0.82, 0.84, 0.86, 0.88, 0.90, 0.92, 0.94, 0.96, 0.98 or 1.00) g: (0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79 or 0.80) g: 40 mL, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0042] In some optional examples, the fourth temperature is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, the hydrothermal reaction time is 8-9h, for example, it can be 8.0h, 8.1h, 8.2h, 8.3h, 8.4h, 8.5h, 8.6h, 8.7h, 8.8h, 8.9h or 9.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] As a preferred technical solution of the present invention, in S4, the mass volume ratio of cyclohexane, Span80, Tween80 and methyltriethoxysilane / quaternary ammonium salt solution is (85-90) g: (10-12) g: (5-7) g: (40-50) mL, for example, it can be (85.0, 85.5, 86.0, 86.5, 87.0, 87.5, 88.0, 88.5, 89.0, 89.5 or 90.0) g: (10.0, 1 48, 49 or 50) mL, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] In some optional examples, the specified pH is 9.5-10, for example, it can be 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the mass ratio of the methyltriethoxysilane to the quaternary ammonium salt is 5:1.
[0047] In some optional examples, the quaternary ammonium salt is quaternary ammonium salt-15.
[0048] In some optional examples, the solvent of the methyltriethoxysilane / quaternary ammonium salt solution is ethanol aqueous solution, and the volume ratio is 1:1.
[0049] In some optional examples, the mass fraction of the methyltriethoxysilane / quaternary ammonium salt solution is 20-25wt.%, for example, it can be 20.0wt.%, 20.5wt.%, 21.0wt.%, 21.5wt.%, 22.0wt.%, 22.5wt.%, 23.0wt.%, 23.5wt.%, 24.0wt.%, 24.5wt.% or 25.0wt.%, but is not limited to the enumerated values, and other unlisted values within this numerical range are equally applicable.
[0050] In some optional examples, the stirring time is 24-25h, for example, it can be 24.0h, 24.1h, 24.2h, 24.3h, 24.4h, 24.5h, 24.6h, 24.7h, 24.8h, 24.9h or 25.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the concentration of the acetic acid solution is 0.1M.
[0052] As a preferred technical solution of the present invention, in S5, the mass volume ratio of the resin matrix, aerogel, ionic liquid composite additive, microsphere additive and solvent is (500-520) g: (80-90) g: (40-45) g: (30-35) g: (120-130) mL, for example, it can be (500, 502, 504, 506, 508, 510, 512, 514, 516, 518 or 520) g: (80, 81, 82, 83, 84, 85) g: (120-130) mL. 5, 86, 87, 88, 89 or 90) g: (40.0, 40.5, 41.0, 41.5, 42.0, 42.5, 43.0, 43.5, 44.0, 44.5 or 45.0) g: (30.0, 30.5, 31.0, 31.5, 32.0, 32.5, 33.0, 33.5, 34.0, 34.5 or 35.0) g: 120 mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] In some optional examples, the solvent is xylene / PMA with a volume ratio of 1:1.
[0054] In a second aspect, the present invention provides an aerogel-reinforced ship antifouling coating prepared by the preparation method described in the first aspect.
[0055] Compared with the prior art, the present invention has the following beneficial effects: (1) the siloxane segments in the fluorosilicone resin matrix and the silanol groups on the surface of the aerogel form covalent bonds through condensation reaction to achieve molecular-level interface bonding, thereby improving the adhesion between the coating and the substrate and resisting the shear stress of water flow. At the same time, the PEEK nanofibers are evenly dispersed in the resin matrix, and their high specific surface area forms extensive hydrogen bonds with the resin, acting as a stress transfer medium to evenly distribute the external load to the aerogel skeleton, thereby reducing the damage of local stress to the adhesion.
[0056] (2) The nanopores of the aerogel and the micron-sized protrusions of the fluorosilicone resin surface layer construct a rough surface, which reduces the wettability of the sticky substances secreted by marine organisms and inhibits initial attachment. The MOF mesoporous structure is loaded with ionic liquids, which blocks the formation of biofilms through ion exchange and coordination bond dissociation. The hollow POSS microspheres expand the shell pores in the seawater environment and release quaternary ammonium salts, achieving efficient killing. DETAILED DESCRIPTION
[0057] The technical solutions of the present invention are described in detail below with reference to specific embodiments. The embodiments described herein are specific embodiments of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be understood as limiting the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments described herein.
[0058] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products and have not been subjected to any further purification treatment.
[0059] Example 1
[0060] This embodiment provides an aerogel-reinforced ship antifouling coating and a preparation method thereof, wherein the preparation method specifically comprises the following steps:
[0061] S1, 300 g of perfluorohexylethyl acrylate, 75 g of KH560, and 2.0 g of azobisisobutyronitrile were mixed, and the mixture was adjusted to 88° C. under a nitrogen atmosphere for reaction for 6.3 h to obtain a fluorosilicone prepolymer. 700 g of the fluorosilicone prepolymer, 300 g of hydroxyl-terminated PDMS, 7 g of dibutyltin dilaurate, and 50 g of PEEK nanofibers were mixed, the mixture was adjusted to 60° C. and stirred for 30 min, and ultrasonically dispersed to obtain a resin matrix;
[0062] S2, 200g of tetraethyl orthosilicate, 220g of ethanol aqueous solution and 4g of 20wt.% ammonia aqueous solution were mixed and hydrolyzed for 24h to obtain SiO2 gel, the SiO2 gel was mixed with 10g of PDMS prepolymer, the temperature was adjusted to 50°C and stirred for 12h to obtain a wet gel, and then solvent replacement was performed to obtain a replacement gel, the replacement gel was immersed in 5wt.% per(heptadecafluorodecyltriethoxysilane)ethanol aqueous solution, the temperature was adjusted to 60°C and stirred for 4h, and vacuum dried to obtain an aerogel;
[0063] S3, dispersing 0.8 g of chromium nitrate nonahydrate and 0.7 g of terephthalic acid in 40 mL of DMF aqueous solution, adjusting the temperature to 150°C for hydrothermal reaction for 8 h to obtain product A, then immersing product A in 20 mL of [BMIM]PF6 methanol solution and vacuum drying to obtain an ionic liquid composite additive;
[0064] S4, 85 g of cyclohexane, 10 g of Span 80, and 5 g of Tween 80 were mixed and adjusted to pH 9.5 with aqueous ammonia. 40 mL of a 20 wt.% methyltriethoxysilane / quaternary ammonium salt solution was added and stirred for 24 h. The mixture was then etched with a 0.1 M acetic acid solution to obtain a microsphere additive.
[0065] S5, mixing 500 g of the resin matrix, 80 g of the aerogel, 40 g of the ionic liquid composite additive, 30 g of the microsphere additive and 120 mL of the solvent to obtain an aerogel-reinforced ship antifouling coating.
[0066] Example 2
[0067] This embodiment provides an aerogel-reinforced ship antifouling coating and a preparation method thereof, wherein the preparation method specifically comprises the following steps:
[0068] S1, 330g of perfluorohexylethyl acrylate, 80g of KH560 and 3.0g of azobisisobutyronitrile were mixed, and the reaction temperature was adjusted to 90°C under a nitrogen atmosphere for 6.0h to obtain a fluorosilicone prepolymer. 730g of the fluorosilicone prepolymer, 340g of hydroxyl-terminated PDMS, 10g of dibutyltin dilaurate and 55g of PEEK nanofibers were mixed, the temperature was adjusted to 65°C and stirred for 40min, and ultrasonic dispersion was performed to obtain a resin matrix;
[0069] S2, 210g of tetraethyl orthosilicate, 230g of ethanol aqueous solution and 5g of 25wt.% ammonia aqueous solution were mixed and hydrolyzed for 25h to obtain SiO2 gel, the SiO2 gel was mixed with 12g of PDMS prepolymer, the temperature was adjusted to 55°C and stirred for 13h to obtain a wet gel, and then solvent replacement was performed to obtain a replacement gel, the replacement gel was immersed in 10wt.% per(heptadecafluorodecyltriethoxysilane)ethanol aqueous solution, the temperature was adjusted to 65°C and stirred for 5h, and vacuum dried to obtain an aerogel;
[0070] S3, dispersing 1 g of chromium nitrate nonahydrate and 0.8 g of terephthalic acid in 40 mL of DMF aqueous solution, adjusting the temperature to 160°C for hydrothermal reaction for 9 h to obtain product A, then immersing product A in 20 mL of [BMIM]PF6 methanol solution and vacuum drying to obtain an ionic liquid composite additive;
[0071] S4, 90 g of cyclohexane, 12 g of Span 80, and 7 g of Tween 80 were mixed and adjusted to pH 9.7 with aqueous ammonia. 44 mL of a 23 wt.% methyltriethoxysilane / quaternary ammonium salt solution was added and stirred for 25 h. The mixture was then etched with a 0.1 M acetic acid solution to obtain a microsphere additive.
[0072] S5, 510 g of resin matrix, 88 g of aerogel, 44 g of ionic liquid composite additive, 33 g of microsphere additive and 120 mL of solvent are mixed to obtain an aerogel-reinforced ship antifouling coating.
[0073] Example 3
[0074] This embodiment provides an aerogel-reinforced ship antifouling coating and a preparation method thereof, wherein the preparation method specifically comprises the following steps:
[0075] S1, 310g of perfluorohexylethyl acrylate, 77g of KH560 and 2.6g of azobisisobutyronitrile were mixed, and the reaction temperature was adjusted to 80°C under a nitrogen atmosphere for 7.0h to obtain a fluorosilicone prepolymer. 710g of the fluorosilicone prepolymer, 330g of hydroxyl-terminated PDMS, 9g of dibutyltin dilaurate and 53g of PEEK nanofibers were mixed, the temperature was adjusted to 64°C and stirred for 33min, and ultrasonic dispersion was performed to obtain a resin matrix;
[0076] S2, 203g of tetraethyl orthosilicate, 225g of ethanol aqueous solution and 4.3g of 22wt.% ammonia aqueous solution were mixed and hydrolyzed for 24.3h to obtain SiO2 gel, the SiO2 gel was mixed with 11g of PDMS prepolymer, the temperature was adjusted to 54°C and stirred for 12.7h to obtain a wet gel, and then solvent replacement was performed to obtain a replacement gel, the replacement gel was immersed in 9wt.% per(heptadecafluorodecyltriethoxysilane)ethanol aqueous solution, the temperature was adjusted to 61°C and stirred for 4.3h, and vacuum dried to obtain an aerogel;
[0077] S3, dispersing 0.9 g of chromium nitrate nonahydrate and 0.73 g of terephthalic acid in 40 mL of DMF aqueous solution, adjusting the temperature to 155°C for hydrothermal reaction for 8.3 h to obtain product A, then immersing product A in 20 mL of [BMIM]PF6 methanol solution and vacuum drying to obtain an ionic liquid composite additive;
[0078] S4, 88 g of cyclohexane, 10.5 g of Span 80, and 6 g of Tween 80 were mixed and adjusted to pH 10 with aqueous ammonia. 48 mL of a 25 wt.% methyltriethoxysilane / quaternary ammonium salt solution was added and stirred for 24.6 h. The mixture was then etched with a 0.1 M acetic acid solution to obtain a microsphere additive.
[0079] S5, 515 g of resin matrix, 90 g of aerogel, 45 g of ionic liquid composite additive, 35 g of microsphere additive and 120 mL of solvent are mixed to obtain an aerogel-reinforced ship antifouling coating.
[0080] Example 4
[0081] This embodiment provides an aerogel-reinforced ship antifouling coating and a preparation method thereof, wherein the preparation method specifically comprises the following steps:
[0082] S1, 320g of perfluorohexylethyl acrylate, 76g of KH560 and 2.3g of azobisisobutyronitrile were mixed, and the reaction temperature was adjusted to 83°C under a nitrogen atmosphere for 6.8h to obtain a fluorosilicone prepolymer. 720g of the fluorosilicone prepolymer, 320g of hydroxyl-terminated PDMS, 8g of dibutyltin dilaurate and 51g of PEEK nanofibers were mixed, the temperature was adjusted to 61°C and stirred for 38min, and ultrasonic dispersion was performed to obtain a resin matrix;
[0083] S2, 207g of tetraethyl orthosilicate, 228g of ethanol aqueous solution and 4.7g of 24wt.% ammonia aqueous solution were mixed and hydrolyzed for 24.6h to obtain SiO2 gel, the SiO2 gel was mixed with 10.5g of PDMS prepolymer, the temperature was adjusted to 52°C and stirred for 12.3h to obtain a wet gel, and then solvent replacement was performed to obtain a replacement gel, the replacement gel was immersed in 7wt.% per(heptadeca)fluorodecyltriethoxysilane ethanol aqueous solution, the temperature was adjusted to 63°C and stirred for 4.7h, and vacuum dried to obtain an aerogel;
[0084] S3, dispersing 0.85 g of chromium nitrate nonahydrate and 0.77 g of terephthalic acid in 40 mL of DMF aqueous solution, adjusting the temperature to 152° C. for hydrothermal reaction for 8.6 h to obtain product A, then immersing product A in 20 mL of [BMIM]PF6 methanol solution and vacuum drying to obtain an ionic liquid composite additive;
[0085] S4, 86 g of cyclohexane, 11 g of Span 80, and 6.5 g of Tween 80 were mixed and adjusted to pH 9.6 with aqueous ammonia. 50 mL of a 21 wt.% methyltriethoxysilane / quaternary ammonium salt solution was added and stirred for 24.2 h. The mixture was then etched with a 0.1 M acetic acid solution to obtain a microsphere additive.
[0086] S5, mixing 520 g of the resin matrix, 83 g of the aerogel, 42 g of the ionic liquid composite additive, 31 g of the microsphere additive and 120 mL of the solvent to obtain an aerogel-reinforced ship antifouling coating.
[0087] Comparative Example 1
[0088] This comparative example provides an aerogel-reinforced ship antifouling coating and a preparation method thereof. The difference between it and Example 1 is that the mass of the aerogel in S5 is 20 g, which is 60 g less than that in Example 1. The other method parameters and operating conditions are exactly the same as those in Example 1.
[0089] Comparative Example 2
[0090] This comparative example provides an aerogel-enhanced ship antifouling coating and a preparation method thereof. The difference between it and Example 1 is that the mass of the ionic liquid composite additive in S5 is 10 g, which is 30 g less than that in Example 1. The other method parameters and operating conditions are exactly the same as those in Example 1.
[0091] Comparative Example 3
[0092] This comparative example provides an aerogel-enhanced ship antifouling coating and a preparation method thereof. The difference between it and Example 1 is that the mass of the microsphere additive in S5 is 5 g, which is 25 g less than that in Example 1. The other method parameters and operating conditions are exactly the same as those in Example 1.
[0093] Adhesion was tested according to GB / T 9286-2021; impact resistance was tested according to GB / T 1732-2020; and biofouling area was tested according to GBT 5370-2007. The test results are shown in Table 1.
[0094] Table 1 Test results of aerogel-enhanced ship antifouling coatings of Examples 1-4 and Comparative Examples 1-3
[0095]
[0096] As shown in Table 1, compared to Example 1, the adhesion and impact resistance of Comparative Example 1 decreased, while the biofouling area increased; the adhesion of Comparative Example 2 remained unchanged, while the impact resistance decreased, and the biofouling area increased; and the adhesion of Comparative Example 3 remained unchanged, while the impact resistance decreased, and the biofouling area increased. Aerogel acts as a reinforcing phase, and its three-dimensional porous structure enhances the interfacial bonding between the coating and the substrate through chemical bonding. The aerogel's nanopores can also disperse impact stress. In Comparative Example 1, the amount of aerogel was reduced, resulting in decreased adhesion and impact resistance, a decrease in the surface fluorination ratio, and an increase in the biofouling area. In Comparative Example 2, the amount of ionic liquid composite additive was reduced, and the MOF carrier had a certain enhancing effect on impact resistance, resulting in decreased impact resistance. Furthermore, insufficient imidazolium cations were released, resulting in an increase in the biofouling area. In Comparative Example 3, the amount of microsphere additive was reduced, while the microspheres had a certain enhancing effect on impact resistance, resulting in decreased impact resistance, a decrease in the quaternary ammonium salt loaded on the microspheres, and an increase in the biofouling area.
[0097] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an aerogel-enhanced ship antifouling coating, characterized in that: The preparation method comprises: S1, mixing perfluorohexyl ethyl acrylate, a silane coupling agent and azobisisobutyronitrile to react to obtain a fluorosilicone prepolymer, and mixing the fluorosilicone prepolymer, hydroxyl-terminated PDMS, dibutyltin dilaurate and PEEK nanofibers to obtain a resin matrix; S2, mixing and hydrolyzing ethyl orthosilicate, an ethanol aqueous solution and an ammonia aqueous solution to obtain a SiO2 gel, mixing the SiO2 gel with a PDMS prepolymer to obtain a wet gel, performing solvent replacement to obtain a replacement gel, and immersing the replacement gel in an ethanol aqueous solution of per(heptadeca)fluorodecyltriethoxysilane to obtain an aerogel; S3, dispersing chromium nitrate nonahydrate and terephthalic acid in a DMF aqueous solution to react to obtain product A, and then immersing product A in a [BMIM]PF6 methanol solution to obtain an ionic liquid composite additive; S4, mixing cyclohexane, Span80 and Tween80, adding methyltriethoxysilane / quaternary ammonium salt solution, and then etching with acetic acid solution to obtain a microsphere additive; S5, mixing the resin matrix, the aerogel, the ionic liquid composite additive, the microsphere additive and the solvent to obtain an aerogel-reinforced ship antifouling coating.
2. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S1: The mass ratio of the perfluorohexylethyl acrylate, the silane coupling agent and the azobisisobutyronitrile is (300-330): (75-80): (2-3).
3. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S1: The mass ratio of the fluorosilicone prepolymer, the terminal hydroxyl PDMS, the dibutyltin dilaurate and the PEEK nanofiber is (700-730): (300-340): (7-10): (50-55).
4. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S2: The mass ratio of the tetraethyl orthosilicate, the ethanol aqueous solution, the ammonia aqueous solution and the PDMS prepolymer is (200-210): (220-230): (4-5): (10-12); The PDMS prepolymer is Sylgard 184.
5. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S2: The solvent replacement is as follows: first, soaking in ethanol for 4-5 hours, changing the solution 3 times, then shaking in ethanol / n-hexane with a volume ratio of 1:1 for 4-5 hours, changing the solution 2 times, and finally soaking in n-hexane for 4-5 hours, changing the solution 2 times.
6. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S3: The mass volume ratio of the chromium nitrate nonahydrate, terephthalic acid and DMF aqueous solution is (0.8-1) g: (0.7-0.8) g: 40 mL.
7. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S4: The mass volume ratio of the cyclohexane, Span80, Tween80 and methyltriethoxysilane / quaternary ammonium salt solution is (85-90) g: (10-12) g: (5-7) g: (40-50) mL.
8. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S4: The mass ratio of the methyltriethoxysilane to the quaternary ammonium salt is 5:1; The quaternary ammonium salt is quaternary ammonium salt-15; The concentration of the acetic acid solution is 0.1M.
9. The method for preparing an aerogel-enhanced ship antifouling coating according to claim 1, wherein: In S5: The mass volume ratio of the resin matrix, aerogel, ionic liquid composite additive, microsphere additive and solvent is (500-520) g: (80-90) g: (40-45) g: (30-35) g: (120-130) mL; The solvent is xylene / PMA, with a volume ratio of 1:
1.
10. An aerogel-reinforced ship antifouling coating obtained according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of terephthalic acid-based ionic liquid catalyst and application of terephthalic acid-based ionic liquid catalyst in PET degradation
CN113578378A
Preparation method of super-hydrophobic silicon dioxide aerogel microspheres
CN113816386A
Synthetic method of POSS nanoparticle enhanced quaternary ammonium salt antibacterial and antifouling silicone rubber
CN116217983A
Long-chain hyperbranched organosilicon polymer antifouling coating grafted with quaternary ammonium salt and preparation method of long-chain hyperbranched organosilicon polymer antifouling coating
CN118406431A
Preparation method of organic silicon antifouling coating of slow-release lubricant
CN119391292A